β-lapachone: A Promising Anticancer Agent with a Unique NQO1 Specific Apoptosis in Pancreatic Cancer - Qadir, Muhammad I.; Iqbal, Muhammad Shahid; Khan, Rimsha (Current Cancer Drug Targets, 2022)
Cancer, one of the major health problems all over the world, requires more competent drugs for clinical use. One recent possible chemotherapeutic drug under research is β-lapachone. β- lapachone (1,2-naphthoquinone) has promising activity against those tumors showing raised levels of Nicotinamide di-phosphate Quinone Oxidoreductases-1 (NQO1). NQO1 is found to be up-regulated in pancreatic tumor cells, and thus β-lapachone could generate cytotoxicity in various cancers like pancreatic tumors. β-lapachone harborage independent growth and clonogenic cell survival in agar. The cell-killing effects of β-lapachone can be stopped by using dicumarol, an inhibitor of NAD(P)H Quinone Oxidoreductases-1. In previously established pancreatic cancer xenografts in mice, β- lapachone inhibited the tumor growth when given orally rather than when combined with cyclodextrin to improve its bioavailability.
Keywords: human pancreatic cancer